A systematic review of flipped classroom empirical evidence from different fields: what are the gaps and future trends?. Issue 2 (3rd June 2019) - Zainuddin, Zamzami; Haruna, Hussein; Li, Xiuhan; Zhang, Yin; Chu, Samuel Kai Wah
Abstract : Purpose: Despite the enhanced popularity of flipped classroom research, there is a lack of empirical evidence reported about the different impacts revealed by the implementation of this concept. Therefore, to respond to this issue, this study aims to review and analyze the trends and contents of flipped classroom research based on 48 studies recently published in 2017 and 2018. The analysis was based on flipped classroom impacts from various fields. Design/methodology/approach: A systematic literature review and content analysis were used as a methodology to investigate positive impacts and challenges of flipped classroom implementation. Findings: The results of the analysis were interpreted using descriptive analysis. Analysis of the impact revealed that the flipped classroom yielded positive impacts on students' learning activities such as academic performance, learning motivation and/or engagement, social interaction and self-directed learning skills. Meanwhile, the most significant challenges encountered by the instructors is a lack of students' motivation to watch the pre-recorded video lectures or to study the contents outside of the class time. Practical implications: Several issues in this discussion become implications that can be taken into consideration for future research. The findings suggest that the flipped classroom concept might be effective in promoting the twenty-first century learning skills. Originality/value: While highlighting the limitations of an ineffective flipped classroom implementation, this study proposes further recommendations for future research.